2016
DOI: 10.1103/physrevb.93.184424
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism of europium under extreme pressures

Abstract: Using synchrotron-based Mössbauer and x-ray emission spectroscopies, we explore the evolution of magnetism in elemental (divalent) europium as it gives way to superconductivity at extreme pressures. Magnetic order in Eu is observed to collapse just above 80 GPa as superconductivity emerges, even though Eu cations retain their strong local 4f 7 magnetic moments up to 119 GPa with no evidence for an increase in valence.We speculate that superconductivity in Eu may be unconventional and have its origin in magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 57 publications
2
21
0
Order By: Relevance
“…Discussion. Both experiment and our calculations concur that Eu retains its f 7 local moment without valence change, 6 and magnetic coupling vanishes at P c . Ev- idently the evolution of the electronic structure plays a critical role by inducing a AFM-MQPM transition.…”
supporting
confidence: 83%
“…Discussion. Both experiment and our calculations concur that Eu retains its f 7 local moment without valence change, 6 and magnetic coupling vanishes at P c . Ev- idently the evolution of the electronic structure plays a critical role by inducing a AFM-MQPM transition.…”
supporting
confidence: 83%
“…While ref. [8] reported that magnetic order disappeared just above 80 GPa, where superconductivity appears according to [1], it should be noted that the experiments in [8] were performed at temperatures higher than 11K, thus not ruling out magnetism at the temperatures considered in [1].…”
Section: C-s-h C-s-hmentioning
confidence: 98%
“…That something 'magnetic' may be going on in the Eu samples studied in [1] is certainly not farfetched given that Eu has a large local moment, is antiferromagnetic at ambient pressure below 90K, and is right next to elements in the periodic table that are ferromagnetic at ambient pressure, Gd below 293K and Tb below 219K. Furthermore a variety of magnetically ordered phases including ferromagneticlike behavior have been detected in Eu under pressure using synchrotron-based Mossbauer and x-ray emission spectroscopies [8]. While ref.…”
Section: C-s-h C-s-hmentioning
confidence: 99%
“…These include electrical transport (Derr et al, 2008;Jaramillo et al, 2010), AC magnetic susceptibility (Debessai et al, 2009;Palmer et al, 2015) and heat capacity/calorimetry (Demuer et al, 2000) for studying the bulk properties of materials under pressure. Nuclear magnetic resonance (Eremets, 1996), Mö ssbauer spectroscopy (Bi et al, 2016), X-ray magnetic dichroism (Duman et al, 2005) and fluorescence (Bi et al, 2016), as well as optical probes (Eremets, 1996), allow characterization of local behavior. We focus in this article on high-pressure X-ray magnetic diffraction in a DAC environment, techniques that have emerged over the last two decades.…”
Section: Introductionmentioning
confidence: 99%